Антология выдающихся достижений в науке и технике. Часть 42: Электроника: ретроспектива, успехи и перспективы ее развития - Баранов, М.И. (Електротехніка і електромеханіка, 2018)
Приведен научно-технический обзор о ретроспективе, успехах, тенденциях и перспективах развития мировой электроники. Рассмотрены основные этапы развития электроники, связанные с изобретением радиолампы, транзистора, интегральной схемы и высокоинтегрированного микропроцессора. Отмечен вклад электронных компаний «Кремниевой долины» США в технологический прорыв в микроэлектронике. Описано состояние работ в области вакуумной
микроэлектроники и наноэлектроники. Наведено науково-технічний огляд про ретроспективу, успіхи, тенденції і перспективи розвитку світової електроніки. Розглянуті основні етапи розвитку електроніки, що пов'язані з винаходом радіолампи, транзистора, інтегральної схеми і високоінтегрованого мікропроцесора. Відмічений внесок електронних компаній «Кремнієвої долини» США в технологічний прорив в мікроелектроніці. Описаний стан робіт в галузі вакуумної мікроелектроніки і наноелектроніки. Purpose. Preparation of brief scientific and technical review
about sources, retrospective view, basic stages, achievements,
problems, trends and prospects of development of world electronics for period of 20th-21st centuries. Methodology. Known
scientific methods of collection, analysis and analytical treatment of the opened scientific and technical information of world
level in area of a vacuum electronics, semiconductor electronics, vacuum microelectronics and nanoelectronics, and also
optical electronics. Results. A brief analytical scientific and
technical review is resulted about the primary and present
states, achievements, trends and prospects of development of
electronics in the developed countries of the world. From positions of approach of the systems advantages and lacks of semiconductor microelectronics are described as compared to a
vacuum electronics. Considerable progress is marked in development of semiconductor element base (microtransistors, microprocessors, microcontrollers and other) for creation of different electronic devices and computing engineering. Information, touching the determining deposit of electronic companies
of the «Silicon Valley» in the USA in providing of technological
breach in area of modern microelectronics, production of computers and their microprocessors, software and creation of devices of mobile communication development, is resulted. The
basic problems of space microelectronics are affected. The possible ways of further development are indicated in the world of
electronics, including vacuum microelectronics and nanoelectronics, and also optical electronics. The special attention is
turned for urgent development of high-efficiency protective facilities specialists against cyber attacks hackers on the computer
systems. In a review an accent is done on the sharp necessity of
acceptance the proper services of drastic measures for a fight
with cyber terrorism. Originality. Systematization of the scientific and technical materials touching world history of development and creation of modern element base of a vacuum electronics and semiconductor microelectronics known from the
sources opened in outer informative space is executed. Possible
new perspective directions of development in the modern world
of microelectronics are formulated. Practical value. Popularization and deepening for students, engineer and technical specialists and research workers of front-rank scientific and technical
knowledge in the topical area of development, creation and
application in the modern technique of the different setting of
high-computer-integrated electronic devices, extending their
scientific range of interests and further development of scientific
and technical progress in society.